Interactions between Halloysite Nanotubes and Poly(styrene sulfonate) in Solution. (28th December 2016) - Kim, Jaeheon; Ryu, Jungju; Shin, Joohuei; Lee, Hoik; Kim, Ick Soo; Sohn, Daewon
Abstract : The interaction between halloysite nanotubes (HNT) and poly(styrene sulfonate) (PSS) in aqueous solution was investigated by dynamic light scattering. Dynamic behavior of HNT/PSS was observed with different salt, HNT, and PSS concentrations. The HNT colloids were stabilized by PSS over a wide range of HNT concentrations, and HNT suspension in dilute solution formed stable HNT/PSS particles. On the other hand, HNT particles aggregated as sediments at higher concentrations due to strong attraction among HNT rods, and HNT aggregates were stabilized by additional PSS. The interactions between HNT and PSS are described by the van der Waals–London force (VDWL). The stabilization process of HNT/PSS particles in salt solution was proposed by comparing the hydrodynamic radii and apparent intensities of samples. The results demonstrate that electrostatic, steric, and depletion stabilization processes are responsible for the stable dispersion of HNT even at high concentration. Abstract :